Effects of the Relatedness of Neighbours on Floral Colour - Torices, Rubén; DeSoto, Lucía; Narbona, Eduardo; Gómez, José María; Pannell, John Richard (Frontiers in Ecology and Evolution, 2021)
The reproductive success of plants depends both on their phenotype and the local neighbourhood in which they grow. Animal-pollinated plants may benefit from increased visitation when surrounded by attractive conspecific individuals, via a ‘magnet effect’. Group attractiveness is thus potentially a public good that can be exploited by individuals, with selfish exploitation predicted to depend on genetic relatedness within the group. Petal colour is a potentially costly trait involved in floral signalling and advertising to pollinators. Here, we assessed whether petal colour was plastically sensitive to the relatedness of neighbours in the annual herb Moricandia moricandioides, which produces purple petals through anthocyanin pigment accumulation. We also tested whether petal colour intensity was related to nectar volume and sugar content in a context-dependent manner. Although both petal colour and petal anthocyanin concentration did not significantly vary with the neighbourhood configuration, plants growing with kin made a significantly higher investment in petal anthocyanin pigments as a result of the greater number and larger size of their flowers. Moreover the genetic relatedness of neighbours significantly modified the relationship between floral signalling and reward quantity: while focal plants growing with non-kin showed a positive relationship between petal colour and nectar production, plants growing with kin showed a positive relationship between number of flowers and nectar volume and sugar content. The observed plastic response to group relatedness might have important effects on pollinator behaviour and visitation, with direct and indirect effects on plant reproductive success and mating patterns, at least in those plant species with patchy and genetically structured populations.